Investigation of proteomic profiles in canine lymphoma using tandem mass tag-based quantitative proteomics approach - Piyanoot Fonghem; Trairak Pisitkun; Kasem Rattanapinyopituk; Sirintra Sirivisoot; Anudep Rungsipipat (Veterinary World, 2022)
Background and Aim: Specific tumor biomarkers are useful for the early diagnosis of cancer or can predict the recurrence of neoplastic disease in humans and animals. Lymphoma in dogs could be classified into B-, T-, and NK-cell origins. T-cell lymphoma has the worst prognosis with a shorter survival time and disease-free interval. This study aimed to identify the differential serum protein expressions of canine B- and T-cell lymphomas compared with healthy dogs using a tandem mass tag (TMT)-based quantitative proteomics.